Circulating tumor cells and extracellular vesicles as liquid biopsy markers in neuro-oncology: prospects and limitations. (11th November 2022) - Westphal,, Manfred; Pantel, Klaus; Ricklefs, Franz L; Maire, Cecile; Riethdorf, Sabine; Mohme, Malte; Wikman, Harriet; Lamszus, Katrin
Abstract: For many tumor entities, tumor biology and response to therapy are reflected by components that can be detected and captured in the blood stream. The so called "liquid biopsy" has been stratified over time into the analysis of circulating tumor cells (CTC), extracellular vesicles (EVs), and free circulating components such as cell-free nucleic acids or proteins. In neuro-oncology, two distinct areas need to be distinguished, intrinsic brain tumors and tumors metastatic to the brain. For intrinsic brain tumors, specifically glioblastoma, CTCs although present in low abundance, contain highly relevant, yet likely incomplete biological information for the whole tumor. For brain metastases, CTCs can have clinical relevance for patients especially with oligometastatic disease and brain metastasis in cancers like breast and lung cancer. EVs shed from the tumor cells and the tumor environment provide complementary information. Sensitive technologies have become available that are able to detect both, CTCs and EVs in the peripheral blood of patients with intrinsic and metastatic brain tumors despite the blood brain barrier. In reference to glioblastoma EVs, being shed by tumor cells and microenvironment and being more diffusible than CTCs may yield a more complete reflection of the whole tumor compared to low-abundance CTCs representing only a fraction of the multiclonal tumor heterogeneity. We here review the emerging aspects of CTCs and EVs as liquid biopsy biomarkers in neuro-oncology.